The introduction and implementation of open dialogue in a day center in Athens, Greece: experiences and reflections of mental health professionals - Skourteli, Marina Christina; Issari, Philia; Dimou, Lito; Antonopoulou, Ariadni O. A.; Bairami, Georgia; Stefanidou, Artemis; Kouroglou, V.; Stylianidis, Stelios (Frontiers in Psychology, 2023)
The present study is part of a large-scale original action-research project aiming to assess the introduction and implementation of the Open Dialogue approach within the clinical practice of an established multidisciplinary team in a Day Centre in Athens, Greece. More specifically, it aimed to explore the experiences of professionals within the process of implementation both in relation to their clinical practice and their professional identity. Data collection employed a focus group, which was set up to explore professional reflections of the implementation and research processes since the introduction of the model. Thematic Analysis of transcripts revealed two main themes that correspond to the impact of Open Dialogue on professionals’ clinical practice and on team dynamics respectively. Professionals identify several challenges in implementing OD, such as difficulties in linking theory to practice, containing uncertainty, and addressing cultural barriers to dialogical ways of working. Professionals further reflect on their own internal journey stemming from the implementation of Open Dialogue that has led them to greater openness and growth, personally and as a team. The role of mental health professionals is being acknowledged as being at the frontline of any meaningful psychiatric reform through the assimilation and promotion of humanistic paradigms aiming towards a change of culture in psychiatric care across different contexts. Despite variations in implementation across different contexts, the importance of consolidating and embracing Open Dialogue as a philosophical framework underpinning mental health care is being discussed.